Experimental study on cascade utilization of ship's waste heat based on TEG‐ORC combined cycle. (7th November 2020) - Liu, Changxin; Ye, Wenxiang; Li, Huaan; Liu, Jianhao; Zhao, Cong; Mao, Zhuofan; Pan, Xinxiang
Summary: The research of ship energy efficiency improvement technology based on waste heat recovery is one of the important solutions for the shipping industry to deal with the increasingly stringent energy efficiency regulations around the world. Traditional thermoelectric power generation (TEG) and organic Rankine cycle (ORC) technologies are difficult to take into account the multiple characteristics of ship waste heat, and the utilization rate is low. In this article, a waste heat cascade recovery system based on TEG‐ORC combined cycle is proposed. The TEG/ORC bottom cycle ratio was defined according to the utilization amount of flue gas waste heat in each bottom cycle. The feasibility of the system was verified by experimental research and the law of system output power, thermal efficiency, multi‐stage waste heat utilization, and cost changing with TEG/ORC bottom cycle ratio was explored under the condition of certain ORC evaporation pressure. In the experiment, a heat pipe enhanced heat exchanger was designed to overcome the heat transfer bottleneck for TEG bottom cycle. TEG‐ORC combined cycle can realize the cascade utilization of various kinds of ship waste heat, optimize the utilization of waste heat, and improve the stability and safety of ORC bottom cycle. It also made the thermal efficiency higher than each bottom cycle and the cost of power generation lower than each bottom cycle. The results shown that when the TEG/ORC bottom cycle ratio was 0.615, the output power of the TEG‐ORC combined cycle experimental system was 134.50 W; the thermal efficiency was 6.93%; the corresponding generation cost was 0.461 $/kWh. Highlights: The TEG‐ORC combined cycle system makes it possible to recover variety of ship waste heat with different properties and temperature ranges. The combined system increases the waste heat utilization rate while reducing the power generation cost. Cascade utilization of flue gas waste heat improves the safety of ORC working medium operation. The thermal efficiency of the TEG‐ORC combined cycle is higher than that of each bottom cycle. Abstract : In this paper, a waste heat cascade recovery system based on TEG‐ORC combined cycle is proposed. It mainly consisted of TEG bottom cycle and ORC bottom cycle. The TEG/ORC bottom cycle ratio was defined according to the utilization amount of flue gas waste heat in each bottom cycle. The law of system output power, thermal efficiency, multi‐stage waste heat utilization and cost changing with TEG/ORC bottom cycle ratio was explored under the condition of certain ORC evaporation pressure.